2006
DOI: 10.1002/jemt.20265
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement and fine structure of collagen fibrils in the decidualized mouse endometrium

Abstract: The adaptations of the mouse uterus to pregnancy include extensive modifications of the cells and extracellular matrix of the endometrial connective tissue that surround the embryos. Around each implanted embryo this tissue redifferentiates into a transient structure called decidua, which is formed by polygonal cells joined by intercellular junctions. In the mouse, thick collagen fibrils with irregular profile appear in decidualized areas of the endometrium but not in the nondecidualized stroma and interimplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
14
0
5
Order By: Relevance
“…Both collagens and Timp proteins are required at the maternal-fetal interface of the placenta (Apte et al 1994;Carbone et al 2006). Together, these data suggest improper ECM formation both within the fetal placenta and the decidua of the PO × BW cross.…”
Section: Discussionmentioning
confidence: 83%
“…Both collagens and Timp proteins are required at the maternal-fetal interface of the placenta (Apte et al 1994;Carbone et al 2006). Together, these data suggest improper ECM formation both within the fetal placenta and the decidua of the PO × BW cross.…”
Section: Discussionmentioning
confidence: 83%
“…In fact, we have previously shown that at least part of the thick collagen fibrils formed during decidualization in the mouse originates by lateral fusion of thin collagen fibrils present in the endometrium before the onset of decidualization (Carbone et al, 2006). Moreover, serial sections of thick fibrils showed that although its central part was homogeneous, close to the surface the fibrils became subdivided into segments (subfibrils), which were often arranged helicoidally along the main fibril (Carbone et al, 2006). It is therefore possible that only type V collagen epitopes situated at the outermost portion of the helical fibrils were accessed by the antibody.…”
Section: Discussionmentioning
confidence: 97%
“…Observation of thin serial sections of decidualized regions of mice uterine horns showed that at least a fraction of the thick collagen fibrils are formed by lateral aggregation of pre-existing thin fibrils (Carbone et al, 2006). However, it is not known whether thin and thick collagen fibrils or both contain more than one distinct collagen molecules.…”
Section: Introductionmentioning
confidence: 98%
“…The region of mature decidual cells showed the thickest fibrils reaching 370 nm in diameter . Neither the genesis nor the role of these large decidual collagen fibrils is known, but some have speculated that they arise by lateral association of smaller diameter fibrils . That they appear to occur only after 9 weeks of gestation and not before suggest a possible stimulus or signal for their formation from the developing embryo, the stimulus or signal being highly localized.…”
Section: Discussionmentioning
confidence: 99%